Cinematherapy Technique for Improving Senior High School Students’ Career Decision-Making Skills in Yogyakarta: A Guidance and Counseling Action Research - Prajaka, Edy; Wangid, Muhammad Nur (Psikopedagogia, 2022)
This action research was performed to improve career guidance service with cinematherapy techniques to improve students’ decision-making skills in SMA Negeri Yogyakarta. Participants were students of Class XII IPS who participated in state university admission tests and found it difficult to make a career decision, particularly regarding the actualization of selecting a major. Twenty-six participants were recruited using a purposive sampling technique. The data were collected using an observation guideline and a questionnaire and analyzed descriptively.   The study was conducted in two cycles, which consisted of planning, implementation, observation, and reflection stages. Career service using the cinematherapy technique was conducted through virtual face-to-face meetings using Zoom. Videos were carefully selected to ensure they could stimulated students to explore, crystallize, select, and clarify the value. Students exhibited poor career decision-making skills before receiving the intervention (mean score: 69). After participating in the cinematherapy, the mean score increased to 75.49 in Cycle I, with clarification, selection, crystallization, and exploration aspects, exhibited score of 73.85, 73.74, 75.27, and 75.13, respectively.   In cycle II, more varied movies were selected, resulting in a mean score of 83.39%, with clarification, selection, crystallization, and exploration showing a score of 83.85, 81.87, 83.30, and 85.64, respectively.   The result showed that career guidance with cinematherapy technique could enhance decision-making skills among Class XII IPS of SMA Negeri 5 Yogyakarta. This study result could be used as an alternative reference to solve students’ issues on career decision-making process